Failure of rituximab is associated with a poor outcome in diffuse large B cell lymphoma‐type post‐transplant lymphoproliferative disorder. (18th February 2020) - Jain, Michael D.; Lam, Ryan; Liu, Zhihui; Stubbins, Ryan J.; Kahlon, Amrit; Kansara, Roopesh; Goswami, Rashmi; Humar, Atul; Prica, Anca; Sehn, Laurie H.; Slack, Graham W.; Crump, Michael; et al.
Summary: Post‐transplant lymphoproliferative disorder (PTLD) may arise after solid organ transplantation, and the most common subtype resembles diffuse large B cell lymphoma (DLBCL). In DLBCL‐type PTLD, the anti‐CD20 antibody rituximab (R) may be combined with chemotherapy (R‐CHOP) or use a strategy (R‐primary; similar to the PTLD‐1 clinical trial) consisting of induction with four weekly doses of R‐alone, without any chemotherapy or sequential R‐CHOP follow‐up. Here we report on a multicentre retrospective cohort of solid organ transplant patients with DLBCL‐type PTLD that were treated with R. In 168 adults, two‐year overall survival (OS) was 63·7% [95% CI (confidence interval) 56·6–71·7%]. No difference in OS was observed, whether patients were treated with R‐CHOP versus the R‐primary strategy. In the 109 patients treated with R‐primary, multivariate analysis found that baseline IPI score and the response to R‐induction predicted OS. Patients who responded to R‐induction had durable remissions without the addition of chemotherapy. Conversely, of the 46 patients who had stable or progressive disease after R‐induction (R‐failure), those who received R‐CHOP had an only marginally improved outcome, with a two‐year OS of 45% (23·1–65·3%) vs. no R‐CHOP at 32% (14·7–49·8%). In real‐world patients, R‐failure and high IPI scores predict a poor outcome in DLBCL‐type PTLD.